Magnolia Extract, Magnolol, and Metabolites: Activation of Cannabinoid CB(2) Receptors and Blockade of the Related GPR55 - Rempel, Viktor (American Chemical Society, 2012)
[Image: see text] The bark of Magnolia officinalis is used in Asian traditional medicine for the treatment of anxiety, sleeping disorders, and allergic diseases. We found that the extract and its main bioactive constituents, magnolol and honokiol, can activate cannabinoid (CB) receptors. In cAMP accumulation studies, magnolol behaved as a partial agonist (EC(50) = 3.28 μM) with selectivity for the CB(2) subtype, while honokiol was less potent showing full agonistic activity at CB(1) and antagonistic properties at CB(2). We subsequently synthesized the major metabolites of magnolol and found that tetrahydromagnolol (7) was 19-fold more potent than magnolol (EC(50) CB(2) = 0.170 μM) exhibiting high selectivity versus CB(1). Additionally, 7 behaved as an antagonist at GPR55, a CB-related orphan receptor (K(B) = 13.3 μM, β-arrestin translocation assay). Magnolol and its metabolites may contribute to the biological activities of Magnolia extract via the observed mechanisms of action. Furthermore, the biphenylic compound magnolol provides a simple novel lead structure for the development of agonists for CB receptors and antagonists for the related GPR55.